Correspondence: Wayne County, GA. - E. B. Rosser, James W. Poppel (Clerk of the Superior Court) - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1895)
Correspondence, Wayne County, 1895. Handwritten Correspondence to E.B. Rosser, Atlanta Georgia with deed from the Brunswick Land and Lumber Company and deed to W.M. Scott. Wayne County, Georgia. November 30, 1895. 1 page.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Court records; Records and correspondence; Wayne County (Ga.)